IDENTIFICATION OF ETHNOSAINS AND LOCAL AWARENESS ABOUT TRADITIONAL JAMU IN MUARA PUTUS, AGAM DISTRICT - Marelda Thaniah; Skunda Diliarosta (SEMESTA: Journal of Science Education and Teaching, 2020)
Research on the transformation of traditional scientific knowledge into scientific science in the production process of traditional herbal medicine. This study aims to transform the original scientific knowledge of the Muara Putus community regarding traditional herbal medicine into scientific science. The benefits expected from this research are as a learning resource or learning model. This research method is descriptive qualitative, in which the researcher is directly involved in the research arena by conducting interviews, discussions, direct observation and studying documents related to traditional herbal medicine, as well as scientific literature related to traditional herbal medicine compounding. The focus of the research is the culture of making traditional herbal medicine focused on the knowledge of herbal medicine sellers regarding the manufacture of herbal medicine, how to mix the herbs, the types of herbal medicine made, and their benefits. The conclusion of this study is that there is some genuine scientific knowledge from herbal medicine sellers that can be explained by scientific science, including the process of making herbal medicine, the ingredients used and the benefits of each herbal medicine.